2021
DOI: 10.2147/ijwh.s303041
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Delayed Initiation and Cessation of Breastfeeding Among Working Mothers in Abu Dhabi, the United Arab Emirates

Abstract: Introduction Despite the enormous benefits of breastfeeding, working mothers face more challenges to meet the World Health Organization (WHO) recommendations regarding successful breastfeeding practices. Little research has been done to understand the breastfeeding practices among working mothers in the United Arab Emirates (UAE). Thus, the aim of this study was to investigate the prevalence and factors associated with delayed initiation and cessation of breastfeeding among working mothers with ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 47 publications
(50 reference statements)
4
20
1
Order By: Relevance
“…Our study showed that the main factors associated with women refraining from EBF were being working women and living in Dubai. This was similar to a study conducted in Abu Dhabi, where 60% of the working women stopped breastfeeding ( 22 ). In the UAE, the women's labor force increased dramatically between 1990 and 2019 at the rates of 28.9 and 52.39%, respectively ( 46 ), and further rose to 57.5 in 2020 according to the World Bank ( 47 ), which increased the number of working women in the UAE.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our study showed that the main factors associated with women refraining from EBF were being working women and living in Dubai. This was similar to a study conducted in Abu Dhabi, where 60% of the working women stopped breastfeeding ( 22 ). In the UAE, the women's labor force increased dramatically between 1990 and 2019 at the rates of 28.9 and 52.39%, respectively ( 46 ), and further rose to 57.5 in 2020 according to the World Bank ( 47 ), which increased the number of working women in the UAE.…”
Section: Discussionsupporting
confidence: 90%
“…This might be because of the number of working hours or duration of maternal leave. In addition to the lack of nurseries in the mother's workplace, making it difficult for working women to breastfeed their infants ( 22 ). Previous studies have also reported that maternal employment was negatively associated with exclusive breastfeeding ( 16 , 48 50 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar findings were reported in other studies [ 44 , 45 ] where it was explained that the reason for less EBF despite high initiation rate among their participants was due to many factors such as employment and deficient knowledge and education about exclusive breastfeeding benefits to mother and infant. So, despite this initial supportive breastfeeding environment in UAE hospitals, our results clearly indicated that hospital policies based on national recommendations are not sufficient to maintain EBF to 6 months postpartum.…”
Section: Discussionsupporting
confidence: 90%